2006
DOI: 10.5144/0256-4947.2006.7
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of sleep problems and habits in a sample of Saudi primary school children

Abstract: BACKGROUNDSleep problems in children vary not only with age, but also with ethnic and sociocultural background. No research has been conducted to assess sleep problems in Saudi elementary school children. This study surveyed parents (or guardians) about their elementary school children’s sleep to assess the prevalence of certain sleep problems.METHODSThe study population comprised boys and girls attending regular public elementary schools in all grades and was conducted during springtime of the year 1999. A qu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

14
58
6
4

Year Published

2011
2011
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 61 publications
(82 citation statements)
references
References 30 publications
14
58
6
4
Order By: Relevance
“…Few studies have earlier controlled for the effect of puberty and studies adequately controlling for confounding variables are called for [17]. Gender [10], socioeco-nomic status [12,13] and puberty [16,30] are factors that can influence both sleep and emotional and behavioral functioning. It has to be noted that although time in bed and insufficient sleep were significantly associated with some symptoms of emotional and behavioral problems, after accounting for shared risk factors, the variance accounted for by emotional and behavioral problems was small; 1.1% for time in bed and 5.7% for sleep sufficiency.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Few studies have earlier controlled for the effect of puberty and studies adequately controlling for confounding variables are called for [17]. Gender [10], socioeco-nomic status [12,13] and puberty [16,30] are factors that can influence both sleep and emotional and behavioral functioning. It has to be noted that although time in bed and insufficient sleep were significantly associated with some symptoms of emotional and behavioral problems, after accounting for shared risk factors, the variance accounted for by emotional and behavioral problems was small; 1.1% for time in bed and 5.7% for sleep sufficiency.…”
Section: Discussionmentioning
confidence: 99%
“…Also low socioeconomic status has been associated with short sleep duration [12,13]. The onset of puberty involves changes at multiple levels and is one factor thatinfluences both sleep and emotional and behavioral problems, however few studies have controlled for this factor.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…12 Wide variations in the reported prevalence of snoring in children have been shown in previously published studies in different parts of the world, ranging from 1.5% to 34.5%. 11,13 Observed differences in reported snoring prevalence may be due to variations in snoring definitions, questionnaires used to elicit the results, and prevalence of obesity in Saudi elementary school children. 11,12,14 The estimated prevalence of narcolepsy with cataplexy in Saudis is 40 per 100,000 people, 15,16 which is within the range reported in other studies that showed the prevalence of narcolepsy with cataplexy to fall between 25 and 50 per 100,000 people.…”
Section: Sleep Medicine In Saudi Arabiamentioning
confidence: 99%
“…Despite a number of surveys in children and adolescents reporting a high prevalence of sleep problems, such as night awakenings [14], nightmares [14], nocturnal enuresis [15], and sleep-onset delay [16], the question of the global subjective perception of sleep quality in childhood has been almost totally neglected. Indeed, only one study on 449 toddlers has directly assessed sleep satisfaction in this population, by means of a question on their global sleep quality perception [17].…”
Section: Introductionmentioning
confidence: 99%